THE DETERMINANT OF SARAWAK BLACK PEPPER PRICE - Alvin, Wong (Universiti Malaysia Sarawak (UNIMAS), 2022)
The objective of this study is to analyse the determinants of the Sarawak black pepper price. This study used secondary data which was from 1985 to 2019. The dependent variable used for the study is black pepper price, while the independent variables are the production of pepper, white pepper price, inflation rate, and official exchange rate (LCU per $US). To achieve the objective of this study, several tests such as the unit root test, including the Augmented Dicky-Fuller (ADF) test and Phillips-Perron (PP) test, Johansen and Juselius Cointegration test, Vector Error Correction Model (VECM), and VECM Granger causality are employed. The ADF test showed that there are two variables to be integrated as I(0), while the PP test showed that there is only one variable to be integrated as I(0). The Johansen and Juselius cointegration test showed that a long-run relationship exists between the dependent variable and independent variable. VECM provided a normalised equation that showed the relationship between the dependent variable and independent variables. White pepper prices have a negative relationship with black pepper prices. Meanwhile, the production of pepper, inflation rates, and official exchange rates have a positive relationship with black pepper prices. However, the inflation rate and the official exchange rate are not significant in determining the black pepper price. Only white pepper price will granger cause black pepper price in the short run, according to VECM Granger Causality.